2016
DOI: 10.15171/hpp.2016.03
|View full text |Cite
|
Sign up to set email alerts
|

Working posture and its predictors in operating room nurses

Abstract: Background: This study was conducted to evaluate working posture of operating room nurses and its relationship with demographic and job details of this group. Methods: This cross-sectional study was conducted among 147 operating room nurses in Tabriz, Iran using a questionnaire and the Rapid Entire Body Assessment (REBA) checklist. The data were analyzed with SPSS.16 using t test, Pearson correlation coefficient and analysis of variance (ANOVA) tests for univariate analysis and the linear regression test for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 15 publications
1
32
0
4
Order By: Relevance
“…Gender, BMI and year of employment of nurses have implications for the incidence of musculoskeletal symptoms [34,35]. The incidence of having at least one musculoskeletal symptoms elevated with age.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Gender, BMI and year of employment of nurses have implications for the incidence of musculoskeletal symptoms [34,35]. The incidence of having at least one musculoskeletal symptoms elevated with age.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…4,6,7 Studies of working posture in dental hygienists have frequently reported problems with maintaining a neutral position in different parts of the body, such as asymmetrical twisting or bilateral height differences in the shoulders or pelvis. [12][13][14] Plantar pressure was developed as a means of measuring the pressure exerted by the sole of the foot during walking and has recently been used as an index of shifts in centre of gravity and balance. [12][13][14] Plantar pressure was developed as a means of measuring the pressure exerted by the sole of the foot during walking and has recently been used as an index of shifts in centre of gravity and balance.…”
mentioning
confidence: 99%
“…[8][9][10] The Rapid Entire Body Assessment (REBA) 11 is an instrument that provides a comprehensive analysis of postural imbalance during working in the shoulders, neck, trunk, back, legs and knees; it is often used to assess working posture in healthcare workers, including dental hygienists. [12][13][14] Plantar pressure was developed as a means of measuring the pressure exerted by the sole of the foot during walking and has recently been used as an index of shifts in centre of gravity and balance. 15 Research on musculoskeletal disorders in dental hygienists has mostly depended on subjective symptoms or only assessed specific body parts.…”
mentioning
confidence: 99%
“…1 Prolonged standing is associated with lower extremity pain or discomfort, swelling, venous disorders, lower back pain, cardiovascular problems, fatigue, and pregnancy complications. 2,[5][6][7] When required to stand for prolonged periods, perioperative team members should use fatigue-reducing techniques, including antifatigue mats to cover hard flooring and standing stools, adjusting the height of the OR bed, ergonomic monitor placement, sit-stand stools, wearing supportive footwear (e.g., closed toed, shock-absorbing), and alternate propping of one foot on a stool. 1 Seven ergonomic tools for such tasks as patient repositioning and transfer maneuvers (e.g., lateral, prone to supine) or those that require prolonged standing or tissue retraction are provided in the full guideline.…”
Section: Individualized Plan Of Carementioning
confidence: 99%